Representations of Loss in Irish Literature (New Directions in Irish and Irish American Literature, 2018)
This is the first book on Irish literature to focus on the theme of loss, and how it is represented in Irish writing. It focuses on how literature is ideally suited to expressions and understanding of the nature of loss, given its ability to access and express emotions, sensations, feelings, and the visceral and haptic areas of experience. Dealing with feelings and with sensations, poems, novels and drama can allow for cathartic expressions of these emotions, as well as for a fuller understanding of what is involved in loss across all situations. The main notion of loss being dealt with is that of death, but feelings of loss in the wake of immigration and of the loss of certainties that defined notions of identity are also analysed. This volume will be of interest to scholars, students and researchers in Irish Studies, loss, memory, trauma, death, and cultural studies.